Adult neurogenesis in the telencephalon of the lizard Podarcis liolepis - González-Granero, Susana; Font, Enrique; Desfilis, Ester; Herranz-Pérez, Vicente; García-Verdugo, José Manuel (Frontiers in Neuroscience, 2023)
In adult lizards, new neurons are generated from neural stem cells in the ventricular zone of the lateral ventricles. These new neurons migrate and integrate into the main telencephalic subdivisions. In this work we have studied adult neurogenesis in the lizard Podarcis liolepis (formerly Podarcis hispanica) by administering [3H]-thymidine and bromodeoxyuridine as proliferation markers and euthanizing the animals at different survival times to determine the identity of progenitor cells and to study their lineage derivatives. After short survival times, only type B cells are labeled, suggesting that they are neural stem cells. Three days after administration, some type A cells are labeled, corresponding to recently formed neuroblasts. Type A cells migrate to their final destinations, where they differentiate into mature neurons and integrate into functional circuits. Our results after long survival periods suggest that, in addition to actively dividing type B cells, there is also a type B subpopulation with low proliferative activity. We also found that new neurons incorporated into the olfactory bulb are generated both in situ, in the walls of the anterior extension of the lateral ventricle of the olfactory bulbs, but also at more caudal levels, most likely in anterior levels of the sulcus ventralis/terminalis. These cells follow a tangential migration toward the olfactory bulbs where they integrate. We hypothesized that at least part of the newly generated neurons would undergo a specialization process over time. In support of this prediction, we found two neuronal populations in the cellular layer of the medial cortex, which we named type I and II neurons. At intermediate survival times (1 month) only type II neurons were labeled with [3H]-thymidine, while at longer survival times (3, 6, or 12 months) both type I and type II neurons were labeled. This study sheds light on the ultrastructural characteristics of the ventricular zone of P. liolepis as a neurogenic niche, and adds to our knowledge of the processes whereby newly generated neurons in the adult brain migrate and integrate into their final destinations.